Classification of Fermi-LAT unassociated sources with machine learning in the presence of dataset shifts - Malyshev, Dmitry (EPJ Web of Conferences, 2025)
About one third of Fermi-LAT sources are unassociated. We perform multi-class classification of Fermi-LAT sources using machine learning with the goal of probabilistic classification of the unassociated sources. A particular attention is paid to the fact that the distributions of associated and unassociated sources are different as functions of source parameters. In this work, we address this problem in the framework of dataset shifts in machine learning.
CRIS-Team Scopus Importer:2025-04-01